The Identification of Key Sector for Sustainable Development in Indonesia: An Extended Input-output Analysis - Imansyah, Muhammad Handry; Putranti, Titi; Muzdalifah (The Indonesian Forestry Certification Cooperation, 2024)
This paper investigates key sectors that can drive sustainable development. Generally, obtaining sustainable development in identifying key sectors for development based on their output multiplier and CO2 emission elasticity. However, one aspect that forgotten is social inclusivity. The present paper has identified seven key sectors with high output multipliers, low CO2 emissions, and try to simulate the potential impact on income distribution. By simulating investment shocks in these sectors, the present authors try to assess their impact on inclusivity, emphasizing the importance of balancing economic growth, environmental protection, and income distribution that meaning social justice within the sustainable development framework. While prioritizing green economy sectors as key drivers can be beneficial, however, there is potential negative impacts on income distribution. Hence, it is recommended that the policy drives green economy sectors by promoting sustainable growth, resource use efficiency, and social inclusivity. This aligns with the core principles of a green economy, ensuring a future that is prosperous, equitable, and environmentally sound.